ANALISIS EKONOMI USAHATANI PADI DAN KELAYAKAN RUMAH TANGGA TANI DI DESA SAMBENG KULON KECAMATAN KEMBARAN KABUPATEN BANYUMAS - Chica Anditia Pratiwi; Dyah Setyorini Gunawan; Istiqomah Istiqomah (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
This study aims to analyze the economic efficiency of rice farming and to measure the contribution of rice farming to total household income and to analyze the living standard of farm households in Sambeng Kulon Village, Kembaran Sub-district, Banyumas Regency. The study was conducted in Sambeng Kulon Village, Kembaran Sub-district, Banyumas District. There were 71 farm households selected by stratified random sampling. The analysis used to calculate the economic efficiency of rice farming is R/C ratio. The contribution of paddy farming to farm household income is obtained by dividing the income earned from rice farming by the total household income multiplied by 100 percent. The living standard is measured by calculating the farm household income divided by the number of dependents in order to get percapita income. This figure is then compared to the regency’s current decent living standard. The results of this study indicate that 1) rice farming in Sambeng Kulon village with an area of ​​≤ 0.5 Ha has a smaller profit (IDR2.718.580) compared with respondents who have land area> 0.5 Ha (IDR7.892.904), 2) the average contribution of rice farming income to farm households with landholding of ​​≤ 0.5 Ha (54,96 percent) is lower than the contribution of rice farming income obtained by respondents with landholding of > 0.5 Ha (77,43 percent), 3) the average income earned by respondents from rice farming (IDR1.624.961,00) is sufficient to meet the average household consumption of IDR 1,379,441.00, and 4) of 71 respondents in Sambeng Kulon Village, 63 respondents live below the decent living standard; after being added with nonfarm income, this figure decreased to 55 respondents. The implication of this research is that the respondents are expected to increase the landholding to increase income earned from rice farming or earn additional nonfarm income so that they can meet household consumption.